Karakteristik Pemekaran Kota Bogor Dan Evaluasinya Terhadap Pola Ruang - Azzam, Muhammad, Drs. H. M. Musiyam, MTP, Dra. Hj. Umrotun, M.Si (2015)
The rising of activities and population growth in Bogor City, are major causes of increased need for land. In order to provide the land, city will tend to spread into areas. This sprending called urban sprawl. This study aims to: (1) determine the urban sprawl characteristics (level, direction and type of urban sprawl) of Bogor City during 2005-2014 and 2) evaluate the suistability between landuse and regional spatial planning in 2014. The secondary data was used to analysis spatial built up areas and survey. Survey method using purphosive sampling. Analysis method using spatial analysis overlay, to get spatial built up areas deviation. Bogor City characteristics of urban sprawl during 2005-214 showed that 35 villages have a vey low-level of urban sprawl, 27 village has a low-level of urban sprawl, 2 villages have a middle-level of urban sprawl, 3 villages have a high-level of urban sprawl and 1 village has a very high-level of urban sprawl. The type of urban sprawl is ribbon development along the main road. Development of built up area during 2005-2014 leads to the south (31.06%) and north (28.62%). Bogor city landuse in 2014 covering 6382,56 Ha (54.50% ) has suitability with regional spatial planning. Land use covering 4.330,57 Ha (36,93 %) has not been realized and land use covering 1.003,86 Ha (8,57%) has unsuitability with regional spatial planning. Class Domination unsuitability is medium-density settlement that located in the low-density settlement of 162.02 ha (16.14%).